ORGANIZATION STAGES AND ADVANTAGES OF THE CASE STUDY METHOD - Usarov Sardor Abdunazirovich (Scholars Digest Publishing, 2023)
This article provides an overview of the case study method and its advantages, as well as teaching methods and techniques, feedback methods and tools, types of cases and their features.
Keywords: type of education, form of education, case study, blended learning.